Further evidence to change the medical classification system of The National Wheelchair Basketball Association - Doyle, T. L. A.; Davies, R. W.; Humphries, B.; Dugan, E. L.; Horn, B. G.; Shim, J. K.; Newton, R. U. (Adapted Physical Activity Quarterly, 2004)
A number of researchers have long questioned systems used for classifying athletes with disabilities. Wheelchair basketball players have gained much attention from researchers. Despite this, no change to the NWBA classification system has been made since it was first adopted in 1984. This study investigated the NWBA classification system. At two summer basketball camps, 46 players were tested to assess player sprint performance and stratification under the NWBA medical classification system. The group consisted of Class 1, 2, and 3 players. Electronic timing gates were used to collect 20 meter sprint-times. Results indicate that Class 1 players were significantly slower compared to Class 2 and 3 players (p < .05) with no difference between Class 2 and 3. The results of this study support a change to this system.